Marketing Strategy to Increase Port Competitiveness - Siti Maemunah; Rio Batista; Anthony Arif Priadi; Rully Indrawan; Eduard Alfian Syamsya Sijabat (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
PT IPC Petikemas Tanjung Priok Jakarta is the service company related to the container terminal sector. The aim of the research is to find out the company’s internal and external factors as well as the company’s strategy to improve its performance especially for the marketing factor. The research method used descriptive method and used SWOT as the data analysis technique. The result in the first quadrant shows an aggressive position. The strategy is using all power it has to take advantage of the existing opportunities. It suggests to formulate the marketing strategies in order to increase the competitiveness of PT IPC Terminal Petikemas and to build the system to improve the effectiveness and efficiency of the operational services. The result also shows that the company should maintain good relation with its customers by giving rewards and discounts, should improve the quality of Human Resources and should create opportunities to develop new innovations. The strategy could be applied through website electronic systems and social media. The company should supervise the operational activities and to promote widely to prepare and overcome the impact of the economic instability.